Konsep Darurat dalam Hukum Islam - Iin Solikhin (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2008)
The important point in Islamic law is justice and punishment. This principal is the reference in deciding an Islamic law. The execution of daru>rah in Islamic law is natural because its priorities the ease and avoiding difficulties. Daru>rah has some meanings. Al-Jassa>s stated as the fear of the damage of soul and body. Daru>rah is something which is related to the big problems which need ease (mashaqqah).",